1975
DOI: 10.1128/iai.11.5.1069-1078.1975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canine distemper virus infection on lymphoid function in vitro and in vivo

Abstract: In the present study, the immunodepressive effects of canine distemper virus (CDV) infection of dogs on two parameters of lymphocyte function, namely phytomitogen-induced cellular proliferation and skin allograft rejection, were investigated. Infection of susceptible gnotobiotic dogs with virulent R252-CDV resulted in a depression of peripheral blood lymphocyte mitogen response as measured by (3H)thymidine incorporation for up to 10 weeks after inoculation. This effect coincided with the appearance of viral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In recent years, viruses have been shown to alter the function of immune cells resulting in modification of the immune response, presumably leading to destruction of the tissue (Zurbriggen and Fujinami, 1989;. It has been shown that CDV causes a marked suppression of lymphocyte function (Krakowka et al, 1975a) but it is not known whether this results in an imbalance of the immune function favoring immunopathological reactions. We have not found evidence for upregulation of class II antigens or TNF alpha in glial cells in distemper in vitro and in vivo (unpublished results), such as has been described in other viral systems (Massa et al, 1987).…”
Section: Virus-induced Modijkations Of Macrophage Functionsmentioning
confidence: 99%
“…In recent years, viruses have been shown to alter the function of immune cells resulting in modification of the immune response, presumably leading to destruction of the tissue (Zurbriggen and Fujinami, 1989;. It has been shown that CDV causes a marked suppression of lymphocyte function (Krakowka et al, 1975a) but it is not known whether this results in an imbalance of the immune function favoring immunopathological reactions. We have not found evidence for upregulation of class II antigens or TNF alpha in glial cells in distemper in vitro and in vivo (unpublished results), such as has been described in other viral systems (Massa et al, 1987).…”
Section: Virus-induced Modijkations Of Macrophage Functionsmentioning
confidence: 99%
“…In several epidemiologic studies measles infections have been shown to occur at a later age in MS patients than controls, particularly in geographic areas where MS is more common (10)(11)(12)(13)(14)(15)(16)(17)38). MV antibodies are frequently elevated in MS serum and CSF whereas lymphocytes from MS patients have a reduced cytotoxic effect on MV infected cells (39). Measles antibodies are elevated to many measles antigens, demonstrated with various serological methods (1,(40)(41)(42).…”
Section: Human Virusesmentioning
confidence: 99%
“…Lymphopenia commonly is present early in the course of the infection. 18 Infection with CDV is initiated by droplet and aerosol exposure. The *Flow Laboratories, McLean, Virginia, and Colab Laboratories, Chicago Heights, Illinois.…”
Section: Canine Distempermentioning
confidence: 99%
“…The *Flow Laboratories, McLean, Virginia, and Colab Laboratories, Chicago Heights, Illinois. 18 Unrestricted spread of the virus results in infection of the respiratory, urogenital, and alimentary tracts and ultimately the brain. Death frequently occurs in these dogs 3 to 4 weeks after infection owing to a demyelinating encephalitis.…”
Section: Canine Distempermentioning
confidence: 99%